2008
DOI: 10.1016/j.ypmed.2008.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents report both positive and negative consequences of experimentation with cigarette use

Abstract: Objective-To examine the physiological and social consequences that 9th and 10th grade adolescents experience as a result of experimenting with cigarette use, and whether consequences vary by level of experimentation and gender.Method-Data were collected between 2001 and 2004 from 395 adolescents attending two northern California public high schools. Analyses are limited to 155 adolescents who reported puffing on cigarettes or smoking whole cigarettes at any of four time points during the study.Results-The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 29 publications
7
21
0
4
Order By: Relevance
“…Additionally, Snedker, Herting, and Walton (2009) found that in disadvantaged neighborhoods, deviant peers have a positive influence on non-drug use; while Winstanley et al (2008) concluded that self-reported neighborhood disorganization and social capital were associated with alcohol or drug use and dependence. Yet other research has found associations between depression, distressed neighborhoods, and drug use disorders (Green and Ensminger 2006;Schinke, Fang, and Cole 2008;van den Bree and Pickworth 2005).…”
Section: Factors Impacting Marijuana Usementioning
confidence: 98%
See 4 more Smart Citations
“…Additionally, Snedker, Herting, and Walton (2009) found that in disadvantaged neighborhoods, deviant peers have a positive influence on non-drug use; while Winstanley et al (2008) concluded that self-reported neighborhood disorganization and social capital were associated with alcohol or drug use and dependence. Yet other research has found associations between depression, distressed neighborhoods, and drug use disorders (Green and Ensminger 2006;Schinke, Fang, and Cole 2008;van den Bree and Pickworth 2005).…”
Section: Factors Impacting Marijuana Usementioning
confidence: 98%
“…These attributes are typically measured as drug use predictors (Anthony 2008;van den Bree and Pickworth 2005). Thus, cumulative risks (i.e.…”
Section: Factors Impacting Marijuana Usementioning
confidence: 99%
See 3 more Smart Citations